Risk Assessment of Intermittent and Continuous Nasogastric Enteral Feeding Methods in Adult Inpatients: A Meta-Analysis - Yang, Guang (Evid Based Complement Alternat Med, 2021)
Diarrhea and pneumonia are common and serious complications in hospitalized patients requiring nasogastric enteral feeding. Our study aimed to compare the risk of diarrhea and pneumonia between intermittent nasogastric enteral feeding (IEF) and continuous nasogastric enteral feeding (CEF). We systematically searched PubMed, Web of Science, and Cochrane for relevant articles published from August 9, 1992, to September 1, 2019. A total of 637 IEF and CEF patients were included in our meta-analysis. Odds ratios (ORs) with associated 95% confidence intervals (CIs) were calculated to estimate the effects of diarrhea and pneumonia. We showed that hospital patients that required IEF had an increased risk of diarrhea compared with CEF. In the subgroup analyses, similar conclusions were identified in the non-China group and small sample size group (size < 100). However, our results showed no significant differences in the China group or large sample size group (size ≥ 100). Furthermore, our analysis showed that no significant association was observed for the risk of pneumonia between IEF and CEF patients. For inpatients requiring nasogastric enteral feeding, CEF is a better method of enteral nutrition compared with IEF, of which patients experience a significantly increased risk of diarrhea.